POLITIK HUKUM PENYEDERHANAAN KELEMBAGAAN PENJAGA LAUT DAN PANTAI DI INDONESIA - Muhammad Naufal Asshidiqie; Dessy Artina; Zulfikar Jayakusuma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
As an archipelagic country with a larger sea area than land, there are challengesin maintaining its territorial sea area. The challenge faced is in the form of efforts inenforcing the law of the sea. Currently, in law enforcement in the Indonesian seas, thereare many institutions that have the same authority and too many laws and regulationsgoverning maritime security in Indonesia. Therefore, the idea arose to simplify theinstitution of sea and coast guards in Indonesia. The purpose of this paper is to find outthe legal politics of simplifying the institutional simplification of Indonesia's sea andcoast guards and to know the implications of simplifying the sea and coast guardinstitutions in Indonesia onthe efficiency of other institutions that have authority in seaand coast guarding in Indonesia.This research is normative juridical, it is based on literature research that takesexcerpts from reading books, or supporting books that have a connection with theproblem to be studied. This study uses secondary data sources consisting of primary,secondary and tertiary legal materials. This study also used qualitative data analysisand produced descriptive data.As for the results of this study, several conclusions can be drawn, namely: First,Law Enforcement in the Indonesian Sea is running ineffectively because manyinstitutions have the same authority in law enforcement in the Indonesian sea. Second,the institutions that have existed will insist on maintaining their respective existences.So it is necessary to integrate maritime security regulations for the effectiveness of lawenforcement in Indonesia's territorial sea areas.Keywords: Simplification-Institutions-Authority